Bone and Lean Mass Loss and Cognitive Impairment for Healthy Elder Adults: Analysis of the Nutrition and Health Survey in Taiwan 2013–2016 and a Validation Study With Structural Equation Modeling - Lin, Sheng-Feng; Fan, Yen-Chun; Pan, Wen-Harn; Bai, Chyi-Huey (Frontiers in Nutrition, 2021)
Purpose: Bone and lean mass loss and cognitive impairment are prevalent in the elder adults and have been hypothesized to share a potential link. Methods: This nationwide cross-sectional study systemically sampled elder adults aged ≥ 65 years and conducted the door-to-door survey. The causal diagrams to help decide which covariates were included in the generalized mixed linear models (GLMMs). The structure equation model (SEM) was performed for validation. Results: A total of 535 participants were enrolled and categorized into normal (67.3%), mild cognitive impairment (18.3%), and dementia groups (14.4%). Alongside increasing the severity of cognitive impairment, the bone marrow density and lean mass consistently showed the trend of decreasing values. In GLMMs, significant association was existed between decrease of BMD and MMSE (β = -5.819 score per g/cm2 decrease, P = 0.0305) with adjustment of age, sex, and physical activity. The SEM models confirmed that MMSE was significantly and directly predicted by age (β =−0.1363, P = 0.0003) and BMD (β = 0.1251, P = 0.0006) independently, and indirectly predicted by lean mass (β = 0.1138, P = 0.0003) through the bone density path. Conclusion: In conclusion, an independent association between bone loss and cognitive impairment was existed rather than the confounding effect, and the decrease of lean mass indirectly contributed to cognitive impairment by influencing the bone density.